2017
DOI: 10.1371/journal.pone.0179331
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of child pedestrian injuries along census tract boundaries: Implications for identifying area-based correlates

Abstract: Census tracts are often used to investigate area-based correlates of a variety of health outcomes. This approach has been shown to be valuable in understanding the ways that health is shaped by place and to design appropriate interventions that account for community-level processes. Following this line of inquiry, it is common in the study of pedestrian injuries to aggregate the point level locations of these injuries to the census tracts in which they occur. Such aggregation enables investigation of the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…By combining spatial and non-spatial data [22], GIS contribute to enabling researchers to analyse patterns in more detail, e.g., focusing on PPRTIs. In this vain, Curtis et al [23] used a combination of different geospatial analytical methods, including proximity analysis, kernel density estimation and local Moran's I to examine the geographical distribution of pedestrian injuries in a midsize city in the United States, while Lightstone et al [24] conducted a study in Long Beach, California to locate high-risk areas for children being hit by motor vehicles. The study showed that 65.6% of such accidents occurred on local and so-called collector streets, which are less than 35 ft (10.7 m) wide.…”
Section: Introductionmentioning
confidence: 99%
“…By combining spatial and non-spatial data [22], GIS contribute to enabling researchers to analyse patterns in more detail, e.g., focusing on PPRTIs. In this vain, Curtis et al [23] used a combination of different geospatial analytical methods, including proximity analysis, kernel density estimation and local Moran's I to examine the geographical distribution of pedestrian injuries in a midsize city in the United States, while Lightstone et al [24] conducted a study in Long Beach, California to locate high-risk areas for children being hit by motor vehicles. The study showed that 65.6% of such accidents occurred on local and so-called collector streets, which are less than 35 ft (10.7 m) wide.…”
Section: Introductionmentioning
confidence: 99%
“…Local Moran's I values provide estimates at the spatial unit level [37], and Getis's G calculates the degree of autocorrelation by comparing the neighborhood with the global average. In addition, many studies have also been conducted on the statistical significance of combinations of Moran's I spatial autocorrelations [38,39], and spatial autocorrelation methods are widely used in many fields [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%